Biallelic SLC13A1 loss-of-function variants result in impaired sulfate transport and skeletal phenotypes, including short stature, scoliosis, and skeletal dysplasia - Christina G. Tise; Katie Ashton; Lachlan de Hayr; Kun-Di Lee; Omkar L. Patkar; Emma Krzesinski; Jennifer A. Bassetti; Erin M. Carter; Cathleen Raggio; Andreas Zankl; Anas M. Khanshour; Kristhen N. Atala; et al. (Genetics in Medicine Open)
Purpose: Sulfate is vital for many physiological processes, including the structural and functional maintenance of macromolecules and formation of sulfur-containing compounds essential for cartilage and bone development. SLC13A1 is a sodium-sulfate cotransporter primarily expressed in the kidney, where it mediates sulfate reabsorption and maintenance of circulating sulfate levels. In this study, we characterized the clinical, biochemical, and functional impact of biallelic SLC13A1 nonsense and/or missense variants in individuals presenting with a skeletal phenotype. Methods: Probands were identified by exome or genome sequencing and GeneMatcher. Sulfate levels were quantified using ion chromatography. SLC13A1 missense variants p.(Arg237Cys), p.(Gly448Asp), p.(Leu516Pro), and p.(Tyr582His) were characterized using bioinformatics, molecular modeling, and [35S]-sulfate uptake assays in Madin-Darby canine kidney cells. Results: All probands presented with concern for short stature and were found to have scoliosis and/or skeletal dysplasia. A reduction in plasma sulfate level and/or increase in urinary sulfate excretion was detected in 2 of 2 probands evaluated. Functional studies were consistent with SLC13A1 variants resulting in the complete loss of sulfate transport activity. Conclusion: Biallelic loss-of-function variants in SLC13A1 are a novel cause of skeletal phenotypes in humans with a measurable biomarker. Sulfate measurements should be considered in the clinical interpretation of variants identified in SLC13A1.